Effect of Clogging on the Permeability of Porous Asphalt Pavement. (5th February 2020) - Ma, Yaolu; Chen, Xianhua; Geng, Yanfen; Zhang, Xinlan
Abstract : The purpose of this paper is to report on the drainage of porous asphalt pavement evaluation method suited for use in analyzing clogging effect. To preliminarily reveal the decrease in permeability caused by clogging of permeable asphalt pavement, an innovative device was proposed to evaluate the anisotropy of permeability influenced by clogging, and the maximum drainage capacity without surface ponding can be obtained when the supplied water was controlled. Then, finite element models for asphalt pavements with hydromechanical coupling were proposed based on porous media theory and Biot's theory. The variation in pore water pressure was simulated by considering the decrease in voids and the increase in clogging grains. The results indicate that the internally retained water should not be ignored because the semiconnected voids were filled with water rapidly at the beginning of permeability tests. To avoid surface ponding, the drainage capacity coefficient (DCC) can be used to evaluate the maximum drainage capacity (MDC) influenced by clogging. Moreover, the pore water pressure increased due to the reduction in voids and a high level of clogging. In addition, the peak value of pore water pressure is also affected by the upper-layer height of the pavement. Under the action of clogging and driving load, a reasonable thickness of the upper layer and a drainage evaluation should be considered to improve road safety.